Altruism as Moderation on Zakat Literacy, Trust, and Religiosity Toward the Decision of Muzakki to Pay Zakat at LAZ Solopeduli - Agus Hidayat, Ahmad; Rizal, Muhamad; Arie Novita, Siska; Shinta Hardiyanti, Istiqom (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Purpose: This research aims to examine the variables of zakat literacy, trust, and religiousness on Muzakki's decision to pay zakat at LAZ Solopeduli. The study also seeks to explore whether altruism can moderate these three variables in influencing Muzakki's decision to pay zakat at LAZ Solopeduli.Design/Method/Approach : This study utilizes a quantitative method assisted by SEM-PLS software to test statistical hypotheses. The sample size consists of 105 Muzakki respondents.Findings: The research findings indicate that zakat literacy, trust, and religiousness have a positive and significant impact on Muzakki's decision to pay zakat. However, the altruism variable is unable to moderate zakat literacy, trust, and religiousness in influencing Muzakki's decision to pay zakat. On the other hand, the religious obligations and basic understanding of zakat drive Muzakki to consistently pay zakat at LAZ Solopeduli, not influenced by other factors such as environmental conditions or altruistic attitudes.Originality/Values: This study is the first to introduce altruism as a variable to examine Muzakki's decision to pay zakat at an official zakat institution